Pengaruh Debt to Equity Ratio (DER), Return on Asset (ROA), Current Ratio (CR), dan Size terhadap Price to Book Value (PBV) pada PT. Astra Internasional Tbk - Nurul Fadillah; Kartin Aprianti; Aris Munandar (Yayasan Jompa Research and Development, 2026)
This study aims to analyze the effect of Debt to Equity Ratio (DER), Return on Asset (ROA), Current Ratio (CR) and Size on Price Book Value (PBV) at PT Astra International Tbk, both partially and simultaneously, and to determine the most dominant variables influencing Price Book Value. This research is an associative quantitative study. The sample in this study is the financial report data of PT Astra International Tbk for 10 years from 2015 to 2024 that meets the criteria of the research variables (DER, ROA, CR, and PBV). This study uses secondary data, namely data obtained from the published annual financial reports of PT Astra International Tbk which include financial position reports consisting of current assets, total assets, current liabilities, total liabilities, equity, and income statements consisting of net income, and the number of shares outstanding for the period 2015–2024. The results of the study indicate that Debt to Equity Ratio (DER), Return on Assets (ROA), and Current Ratio (CR) do not have a significant partial effect on Price Book Value, only (Company Size) is proven to have a significant effect on Price Book Value. Simultaneously, Debt to Equity Ratio, Return on Assets, Current Ratio, and Company Size are proven to have a significant effect on Price Book Value. This indicates that good financial performance from various aspects will increase investors' positive perceptions of the company and have an impact on increasing the company's value.